Long Journey Home - Branka Kovačević ([sic])
Australian literature, as one of the vital constituents of English-speaking literature, boasts a rich diversity of themes and style, as does the society and continent on which it is located. It is rooted in an ancient landscape, which carries some of the oldest cultural traditions, as well as a mixture of numerous cultural immigrants. Ever since Patrick White received the Nobel Prize for Literature in 1973, the literary critical public has turned its attention to the South, toward a distant and mystical land where contemporary writers who play with the aesthetic principles of the Western Circle have begun to emerge and remain loyal to Australia, attempting to understand and, at the same time, defining Australian culture – or a variety of its cultures. Until recently, a small number of scholars from Serbia and the neighboring countries approached the study of Australian literature. Theoretical concern for the Australian literature never substantially advanced our understanding of this rich literary tradition, and the availability of critical literature on Australian literary production was limited. Therefore, a true refreshment for the critical public and readers of Australian literature was brought by an inspired theoretical and interpretive study written by Tijana Parezanović, entitled Terra Australis: Mitopoetika pripadanja (The Mythopoesis of Belonging), which was published (in Serbian) in 2019 by Alfa BK University.